CIVIL LIABILITY OF NURSES IN THERAPEUTIC AGREEMENTS IN LAW NO. 17 OF 2023 AND EFFORTS TO PREVENT VIOLATIONS OF THE LAW IN THERAPEUTIC AGREEMENTS - Bambang Fitrianto (PT. Sinergi Legal Publisher, 2025)
Nurses have a very important role in supporting the quality of hospital services and public health services. Nurses are the spearhead and are often used as indicators of the quality of health services and play a role in determining the level of patient satisfaction. However, in practice, it is possible that negligence or errors made by health workers can occur which can have fatal consequences for patients. In this regard, nurses as medical personnel cannot be separated from the legal consequences of therapeutic transactions carried out as accountability for losses arising from negligence by health workers in carrying out service duties, this is regulated in Article 308 of Law No. 17 of 2023 concerning Health. The purpose of writing this journal is to determine the legal consequences of therapeutic transactions as civil liability for nurses in public health services. The method used in this thesis is normative legal research, with data collection through library research and related laws and regulations. Based on the results of the research conducted, the legal consequences of therapeutic transactions as civil liability for nurses in public health services are that health workers working in hospitals are also held legally accountable if they meet the requirements as stated in Article 308 of Law No. 17 of 2023 concerning Health, namely: Medical Personnel and Health Personnel who are held accountable for actions/deeds related to the implementation of Health Services that are detrimental to Patients in a Civil Law. Thus, civil liability in a therapeutic health service agreement, the perpetrator can be sued on the basis of breach of contract for the medical agreement made (Article 1243 of the Civil Code) and unlawful acts (Article 1365 of the Civil Code) if they have received a recommendation from the professional disciplinary council as Article 304 of Law No. 17 of 2023.